Monetary policy shocks and Islamic banks' deposits in a dual banking system: empirical evidence from Malaysia and Bahrain - Mohd Yusof, Rosylin; Al Wosabi, Mohammed; Abd. Majid, M. Shabri (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2009)
The objective of this paper is to empirically explore the dynamic inter-relationships between deposits of Islamic banks with monetary policy variables in Bahrain and Malaysia covering are being dubbed as the worlds' largest International Islamic Financial Hubs (Qorchi, 2005). A comparative analysis between these two countries highlights the differences and similarities of the impact of monetary policy shocks on the Islamic banks' deposits. The analysis comprises of two major testing approaches. First, the auto-regressive distributed lag (ARDL) model is used to examine the long-run dynamics among the variables. Compared to the Malaysian Islamic banks' deposits, the study finds that the Islamic banks' deposits in Bahrain are sensitive to monetary policy changes. This implies that the Bahraini Islamic banks are less capable of offset the destabilizing impact of monetary policy as compared to its Malaysian counterpart.